O movimento estudantil na Universidade Federal do Espírito Santo : a trajetória de um grupo ao poder (1976-1981) - Moreira, Renato Heitor Santoro (2008)
This work rescues the genesis of what later was constituted as a hegemonic political group in Espírito Santo’s institutional politics. Using oral history, it tries to rebuilt the student movement in Espírito Santo’s Federal College, between 1976 and 1981, when the Student Central Directory was reopened, having as first president, in this new phase, Paulo César Hartung Gomes, a student of the Economics course. The paper presents the political scenery of the period and how Brazil's opposition divisions debates reflected directly on the academy, also comprising discussions in the student movement.